Performance Analysis of Turbine Ventilators for Refugee Camps Usage - M.I.N, Ma'arof; Girma, T. Chala; Shree R., Nair (IAEME Publication, 2019)
A turbine ventilator is a promising technology used to achieve multiple cooling conditions. The present study proposed a method to improve the indoor air quality (IAQ) of refugee camps to overcome issues related to air borne diseases. A turbine ventilator was designed based on the ISO and ASHRAE standards. The effect of the turbine ventilation fan on the IAQ of a modelled refugee shelter was investigated via Computational Fluid Dynamics (CFD) simulation. The first part of the study was intended to select the best turbine ventilator design to test its performance while in the second part, simulation study was conducted on the selected design in comparison with the benchmarks (currently market-available turbine ventilators). It was observed that a 55° blade angle design performed best at 115 RPM and was tested for indoor air quality improvement for the transitional shelter found in the Dadaab region, Kenya. ISO 7730 (2005) standards were met with average internal air velocity of 0.25m/s. PMV and PPD for the whole space were at 0.452 and 9.938%, respectively, which are well within the recommended values. The results from this study would hopefully provide an insight into future developments of turbine ventilators not only for refugee camps, but also for other sectors requiring improvements to indoor air quality.